Resquícios cangaçais um resgate memorial dos bandos anônimos - Soares, Roniere Leite (2005)
The historical rescue of the anonymous cangaçais groups/bands was the way in which we tried to exhibit the public readers in general, the existence of an exaggerated majority omitted intentionally in opposition to the individualized canonization of Lampião as half-finished process of formation discourse. We ve had as general objective to retake the anonymous groups history, carrying through, specifically the tracing small biographies of these groups, grouped through respective cangaceiros leaders, as well as the analysis of the speeches of the interviewed ones. From an interdisciplinary perspective, we intend to guide the text without in arresting to one or another theoretician that could restrict our research to a possible unilateral vision, therefore we chose to work with semiotics, linguistic, historical, discoursives and social elements. Accumulating a range of theoretical visions in face of a subject that, by itself makes us distrust that the interdisciplinarity is nearer to the investigated object than to the investigated citizen, we ve searched for information in plural sources of references such as twines, periodicals, books, cartoons, literary compositions, biographical books, agricultural magazines, countryside environments, cinematographic productions, and also verbal history of the popular interviewed people. We ve decided to base our work according to Le Goff, Walter Benjamin, Eric Hobsbawm, Sharpe (in Peter Burke) and Eni Orlandi. We ve made a northeast contextualization having as reference the representation of the main members of the catholic church, as well as the coronelism and the large state, opposing these institutions in face of the against-institution of cangaço, in the end of the second chapter, in reason of its conceptual crisis. The proposal to elicit/group the considered anonymous groups it made possible to establish small biographies, as we ve had as the main principle of the work a boarding that was centered in the limits of the interpretation, covering the description of the facts and the analysis of the speech of the deponents. We ve had as evidence at the end of the work, that the hypotheses formulated initially had been confirmed with: the discovery of other groups to the group of Corisco, considered, accoding to the official speech, as the last cangaçal group; the ratification that the anonymity of the groups/bands is generally due to the lack of photographic registers; and the register of bands that had covered areas of the wasteland, despite cariri and the hinterland, already mentioned officially.